2006
DOI: 10.1242/dev.02480
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles for Hedgehog and canonical Wnt signaling in specification,differentiation and maintenance of osteoblast progenitors

Abstract: DEVELOPMENT 3231 RESEARCH ARTICLE INTRODUCTIONThe mammalian skeleton forms from three distinct cell lineages (Nakashima and de Crombrugghe, 2003). Facial bones and the cranium are derived from the neural crest. The base of the skull, the parietal bones and the axial elements of the ribs and vertebrae are derived from paraxial mesoderm. The sternum and long bones are formed from lateral plate mesoderm. Although several cell lineages contribute to skeletal structures, each gives rise to a common bone matrix-secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
995
2
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 919 publications
(1,059 citation statements)
references
References 48 publications
47
995
2
3
Order By: Relevance
“…The above data indicates that without a β-catenin signal osteoblasts can not differentiate to an osterix positive stage. When β-catenin was deleted in osterix positive osteoblasts, those cells failed to progress to mature osteoblasts (characterized by high osteocalcin expression) although collagen I, Runx2, and osterix were observed [52]. In summary, the above data suggest that canonical Wnt signaling is required for both osteoblast early differentiation and terminal differentiation.…”
Section: Wnt Signaling In Osteoblastogenesismentioning
confidence: 88%
See 2 more Smart Citations
“…The above data indicates that without a β-catenin signal osteoblasts can not differentiate to an osterix positive stage. When β-catenin was deleted in osterix positive osteoblasts, those cells failed to progress to mature osteoblasts (characterized by high osteocalcin expression) although collagen I, Runx2, and osterix were observed [52]. In summary, the above data suggest that canonical Wnt signaling is required for both osteoblast early differentiation and terminal differentiation.…”
Section: Wnt Signaling In Osteoblastogenesismentioning
confidence: 88%
“…In bone marrow stromal osteoblast cultures, Wnt7b showed a marked increase in its expression after induction of differentiation [85]. An initial report on the Wnt7b −/− E18.5 embryo did not show any clear skeletal phenotype [52]. However, ablation of Wnt7b from skeletal progenitors by using CreloxP technique with Dermo1-Cre results in a deficiency in embryonic bone formation, which is at least partly due to a deficit in osterix activation and subsequent osteoblast differentiation [86].…”
Section: Wnts-reporter Mouse Strains For Active Canonical Wnt Signalimentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of β-catenin in early skeletal progenitor cells causes osteoblast precursors to become chondrocytes [13][14][15]. Inactivation of β-catenin in committed osteoblast progenitors prevented the expression of osteoblast-specific genes, indicating that β-catenin is also essential for osteoblast differentiation [15,16]. Mice with β-catenin removal in mature osteoblasts displayed severe osteopenia, which surprisingly was due to an increase in osteoclasts [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that osterix acts downstream of Runx2 (Franceschi et al, 2007). Considerable evidence has revealed that Wnt up-regulates the expression of both Runx2 and osterix (Bennett, 2005;Rodda and McMahon, 2006). Consequently, it is likely that suppression of osterix is associated with a reduction in postnatal development in mutant mice.…”
Section: Discussionmentioning
confidence: 99%